Epithelial Keratins Modulate cMet Expression and Signaling and Promote InlB-Mediated Listeria monocytogenes Infection of HeLa Cells - Cruz, R (2018)
The host cytoskeleton is a major target for bacterial pathogens during infection. In particular, pathogens usurp the actin cytoskeleton function to strongly adhere to the host cell surface, to induce plasma membrane remodeling allowing invasion and to spread from cell to cell and disseminate to the whole organism. Keratins are cytoskeletal proteins that are the major components of intermediate filaments in epithelial cells however, their role in bacterial infection has been disregarded. Here we investigate the role of the major epithelial keratins, keratins 8 and 18 (K8 and K18), in the cellular infection by Listeria monocytogenes. We found that K8 and K18 are required for successful InlB/cMet-dependent L. monocytogenes infection, but are dispensable for InlA/E-cadherin-mediated invasion. Both K8 and K18 accumulate at InlB-mediated internalization sites following actin recruitment and modulate actin dynamics at those sites. We also reveal the key role of K8 and K18 in HGF-induced signaling which occurs downstream the activation of cMet. Strikingly, we show here that K18, and at a less extent K8, controls the expression of cMet and other surface receptors such TfR and integrin β1, by promoting the stability of their corresponding transcripts. Together, our results reveal novel functions for major epithelial keratins in the modulation of actin dynamics at the bacterial entry sites and in the control of surface receptors mRNA stability and expression.